Comparison of strain and stress conditions in conventional and ARB rolling processes - Kocich, Radim; Macháčková, Adéla; Fojtík, František (International journal of mechanical sciences, 2012)
The presented paper outlines the procedure and certain results of the experimental analysis of the strain and stress conditions in a billet during flat rolling. The photo-plasticity method of experimental stress analysis was used to solve the concerned problems. This application for evaluating stress and strain conditions allows to determine the directions as well as the differences of the main strains in the deformed material. The obtained data can then be used to deal with the static conditions of equilibrium by applying the shear stress difference method and the successive approximation method. What exists among the specified results is the comparison of experimental source materials obtained under both the conventional rolling process and multi-layer material rolling (the basis of the accumulative roll bonding process). The main attention was focused on the stress and strain conditions in both procedures. ► The analysis of the strain/stress conditions under flat rolling was executed. ► The real deformation zone is substantially larger than the geometric zone. ► The tensile stresses that may cause rupture of the rolled billets. ► Gap between layers of the material under the ARB process is due to tensile stresses. ► Behaviour of the material during ARB and conventional rolling is not the same.